Transbrachial Access for Transcatheter Closure of Paravalvular Leak Following Prosthetic Valve Replacement - Zhang, Hui; Wang, Jing-Yan; Lv, Jian-Hua; Hu, Hai-Bo; Xie, Rui-Gang; Jin, Qi; Pang, Kun-Jing; Xu, Liang; Xu, Zhong-Ying; Zhang, Ge-Jun; Pan, Xiang-Bin (Frontiers in Cardiovascular Medicine, 2021)
Abstract: Background: Transcatheter closure of paravalvular leak (PVL) has evolved into an alternative to surgery in high-risk patients. In this study, we introduce a new access for transcatheter closure of PVL and seek to evaluate the feasibility and safety of this access. Methods: We retrospectively analyzed patients undergoing transbrachial access for transcatheter mitral or aortic PVL closure (August 2017-November 2019) at our hospital. All patients underwent puncture of the brachial artery under local anesthesia. Results: The study population included 11 patients, with an average age of 55.91±14.82 years. Ten out of 11 patients were successfully implanted with devices via the brachial artery approach, and one patient was converted to the transseptal approach. The technical success rate of transbrachial access was 90.9%. Mean NYHA functional class improved from 3.1±0.5 before the procedure to 1.9±0.5 after PVL closure. Severe paravalvular regurgitation (PVR) in five patients and moderate PVR in six patients prior to the procedure were significantly reduced to mild in four patients and none in seven patients after the procedure. Complications included one case of pseudoaneurysm and one case of moderate hemolysis aggravation after closure. One patient had an unknown cause of sudden death within 24 h after the procedure. The half-year mortality rate during follow-up was 9.1% (1/11). Conclusions: Transbrachial access for transcatheter closure of PVL may be a feasible and safe treatment and should include well-selected patients. It has several potential advantages of simplifying the procedure process and reducing postprocedural bed rest time.